Mini treats & hand-held sweets : 100 delicious desserts to pick up and eat - Dodge, Abigail Johnson (The Taunton Press, 2012)
"This book, a collection of homemade finger sweets from baking expert Abby Dodge, emphasizes solid baking techniques, fresh ingredients, and popular flavors while exploring flavor pairings that complement each dessert's alluring character"--